Locomotion study and improvement of multi-legged robots involving CG adjustment - Chen, Wenjie. (2008)
There is a growing demand in recent years for multi-legged robots to travel on natural terrain with superior locomotion behaviors such as good stability and terrain-adaptability. However, these demanding specifications are not always compatible when legged robots walk on terrain containing a lot of forbidden zones. This thesis is aimed to present and investigate the CG (Center of Gravity) adjustment methods, and provide strategies to improve legged machines' comprehensive (static and dynamic) locomotion behaviors on rough terrain.